Abstracts Accepted for Publication 2019
DOI: 10.1136/annrheumdis-2019-eular.3808
|View full text |Cite
|
Sign up to set email alerts
|

Ab1049 co-Morbidity Index in Children With Systemic Lupus Erythematosus

Abstract: BackgroundComorbid conditions in patients with rheumatic diseases (RD) aggravate the course of diseases, worsen the prognosis, impede the response to therapy, and reduce the quality of life of patients. Initial manifestations of comorbid lesions of organs and systems are already manifested in childhood and adolescence, and in the future are the causes of persistent morphologic and functional disorders, disability and mortality of patients.ObjectivesThe purpose was to identify comorbid conditions in children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 45 A study on the comorbidity index in children with SLE also indicated that it is not uncommon for the initial manifestations of comorbid lesions in organs and other systems to occur in children and adolescents, potentially leading to continuous morphological and functional disorders, morbidity and mortality in children. The underlying mechanism responsible for developing the above comorbid conditions might be associated with the disruption of lipid metabolism and blood coagulation 46 and deserves further confirmation in future studies.…”
Section: Discussionmentioning
confidence: 90%
“… 45 A study on the comorbidity index in children with SLE also indicated that it is not uncommon for the initial manifestations of comorbid lesions in organs and other systems to occur in children and adolescents, potentially leading to continuous morphological and functional disorders, morbidity and mortality in children. The underlying mechanism responsible for developing the above comorbid conditions might be associated with the disruption of lipid metabolism and blood coagulation 46 and deserves further confirmation in future studies.…”
Section: Discussionmentioning
confidence: 90%